2021
DOI: 10.3390/biomedicines9030242
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Affects HDL Metabolism, Composition and Subclass Distribution

Abstract: Background: Obesity increases the risk of coronary heart disease, partly due to its strong association with atherogenic dyslipidemia, characterized by high triglycerides and low high-density lipoprotein (HDL) cholesterol levels. Functional impairment of HDL may contribute to the increased cardiovascular mortality, but the effect of obesity on composition, structure, and function of HDL is not well understood. Design and Methods: We determined HDL composition, HDL subclass distribution, parameters of HDL functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 71 publications
4
30
0
Order By: Relevance
“…Similar to the findings of Trimigno et al, Pasiakos et al reported that lower-BMI subjects have higher HDLchol levels at high-protein diets [51], which indicates that high-BMI subjects potentially have a higher risk of CVD as HDLchol is recognized as good cholesterol [52]. The higher risk of CVD for overweight subjects has also been related to impaired HDLchol metabolism [53]. Schmedes et al concluded that weight loss decreases both the levels of LP in plasma and SCFA in fecal samples [54].…”
Section: Discussionsupporting
confidence: 61%
“…Similar to the findings of Trimigno et al, Pasiakos et al reported that lower-BMI subjects have higher HDLchol levels at high-protein diets [51], which indicates that high-BMI subjects potentially have a higher risk of CVD as HDLchol is recognized as good cholesterol [52]. The higher risk of CVD for overweight subjects has also been related to impaired HDLchol metabolism [53]. Schmedes et al concluded that weight loss decreases both the levels of LP in plasma and SCFA in fecal samples [54].…”
Section: Discussionsupporting
confidence: 61%
“…However, several chronic diseases are associated with profound alterations in HDL metabolism and function, caused by increased systemic oxidative stress and inflammation ( 12 , 54 ). These conditions include obesity ( 55 57 ), chronic kidney disease ( 58 , 59 ), liver disease ( 60 , 61 ), diabetes ( 62 64 ), CVD ( 65 , 66 ), but also allergic rhinitis ( 67 ) and skin diseases ( 68 , 69 ). Compositional modifications and concomitant changes in parameters of HDL function may lead to development of pro-atherogenic characteristics and enhancement of the inflammatory state.…”
Section: Hdl Structure Composition and Functionmentioning
confidence: 99%
“…It has been shown that obesity affected the lipid composition of HDL particles, increased acute phase protein serum amyloid a, and altered HDL particle subpopulations. Moreover, HDL of obese subjects showed prooxidative properties [ 25 ]. Because of higher obesity indices values in the NAFLD group and a significant relationship between impaired anti-inflammatory capacity of apoB-depleted plasma and obesity indices in the current study, we sought to determine if the association between impaired HDL anti-inflammatory capacity and NAFLD is related to obesity.…”
Section: Discussionmentioning
confidence: 99%